⎩ ⎨ ⎧ x y = 3 0 − y x x x = 3 5 − y y Let x and y be positive real numbers satisfying the system of equations above. Find x 2 + y 2 + 3 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good solution
I did it the same way...
Nice way of thinking. Up voted.
{ x y = 3 0 − y x x x = 3 5 − y y . . . ( 1 ) . . . ( 2 )
( 1 ) : x y x y + y x a 2 b + a b 2 ⇒ a b ( a + b ) α β = 3 0 − y x = 3 0 Let a = x and b = y = 3 0 = 3 0 Let α = a + b and β = a b = 3 0
( 2 ) : x x x x + y y a 3 + b 3 ( a + b ) ( a 2 + b 2 − a b ) ( a + b ) [ ( a + b ) 2 − 3 a b ] α 3 − 3 α β α 3 − 3 ( 3 0 ) ⇒ α 3 α ⇒ β = 3 5 − y y = 3 5 = 3 5 = 3 5 = 3 5 = 3 5 = 3 5 = 1 2 5 = 5 = 6
Now we have:
x 2 + y 2 + 3 = a 4 + b 4 + 3 = ( a + b ) ( a 3 + b 3 ) − a b ( a 2 + b 2 ) + 3 = 3 5 α − β ( α 2 − 2 β ) + 3 = 3 5 ( 5 ) − 6 ( 5 2 − 2 ( 6 ) ) + 3 = 1 0 0 = 1 0
Though slightly lengthy but provides again a new way to look into problems...
Rewrite the 2 equations:
x y + y x = 3 0
x x + y y = 3 5
Square both equations:
x 2 y + 2 x y x y + x y 2 = 3 0 2
x 3 + 2 x y x y + y 3 = 3 5 2
Subtract: x 3 − x 2 y + y 3 − y 2 x = 3 5 2 − 3 0 2 = 3 2 5
Grouping: ( x − y ) ( x 2 − y 2 ) = ( x + y ) ( x − y ) 2 = 3 2 5
The only square factors of 325 are 1 and 25, but 1 will not work. So this diophantine equation can only have 2 solutions that can be yielded from:
x + y = 1 3
x − y = ± 5
Yay ! Same method .
Adding and subtracting the equations ,we get
( x − y ) ( x − y ) = 5 and ( x + y ) ( x + y ) = 6 5
Multiplying them, ( x 2 − y 2 ) ( x − y ) = 6 5 × 5
Let, ( x 2 − y 2 ) = 6 5 and ( x − y ) = 5 ⇒ x = y + 5
( y + 5 ) 2 − y 2 = 6 5 ⇒ y = 4 Therefore, x = 4 + 5 = 9
x 2 + y 2 + 3 = 9 2 + 4 2 + 3 = 1 0 0 = 1 0
F o r e a s e o f c a l c u l a t i o n s , l e t a = x , a n d b = y . ∴ T h e t w o e q u a t i o n s a r e : − ( A ) a 3 + b 3 = 3 5 , ( B ) a b ( a + b ) = 3 0 . A n d ( C ) x 2 + y 2 + 3 = a 4 + b 4 + 3 . F r o m ( A ) a 3 + b 3 = 2 7 + 8 = 3 3 + 2 3 = 3 5 . ∴ a = 3 a n d b = 2 . S u b s t i t u t i n g i n ( B ) , L H S = 3 ∗ 2 ( 3 + 2 ) = 3 0 = R H S . S o a I S E Q U A L T O 3 a n d b I S E Q U A L T O 2 . ⟹ a 4 + b 4 + 3 = 8 1 + 1 6 + 3 = 1 0 . F r o m ( C ) x 2 + y 2 + 3 = 1 0 .
Its all quite simple if you can visualise what exactly it needs. Though its a hit and trial but its works quite often. Lets take x=9 and Y = 4. Its statifies both the equations and hence, The answer is 10.
Problem Loading...
Note Loading...
Set Loading...
⇒ x y = 3 0 − y x
x y + y x = 3 0
⇒ x x = 3 5 − y y
x x + y y = 3 0 + 5
x x + y y = ( x y + y x ) + 5
x x − y x + y y − x x = 5
x ( x − y ) − y ( x − y ) = 5
( x − y ) ( x − y ) = 1 × 5
Now by comparing,
We get x = 9 and y = 4 .
Putting these values in x 2 + y 2 + 3 .
( 9 ) 2 + ( 4 ) 2 + 3 = 1 0 0 = 1 0